Investigation of Mathematical Modeling for Banana Slices Drying using Hot Air Technique - Dongbang, Watcharin; Nuantong, Weerapon (Asian Health, Science and Technology Reports, 2020)
The parameter models of banana slices drying are very important for predicting to approximate the mathematical. This paper demonstrates the drying kinetics with mathematical modeling of banana slices drying using hot air technique. The banana slices were dried the temperature about of 60–70°C and 0.8 m/s for the hot air velocity. The parameters were studied the banana slices thickness of 2–6 mm and 300% db for initial moisture content. An experimental result was presented in terms of moisture content and shrinkage. The drying time was revealed about of 180–220 minutes which the temperature affected the moisture content and shrinkage of banana slices. The moisture diffusivities were presented of 1.42-13.5×10-10m²/s. In addition, the moisture ratio was applied to generate the drying models of banana slices which the Page model to be the best model.